Enhanced anti-theft safety box system for home application - Azman, Muhammad Alif; M. Zin, Nor Affida; Mohamad, Nurul Nadia; Abd. Hamid, Fatimah Khairiah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Conventional or traditional safe lock systems frequently have inadequate security and access control mechanisms. The lack of advanced components makes it more difficult to safeguard against modern burglary techniques and unauthorized access attempts. This could result in breaches and compromised security for valuable assets. The proposed solutions for the currently existing issues in safe lock systems include the use of IoT-based sensor systems to automate security and provide real-time monitoring, ensuring robust protection against unauthorized access. Hence, this technical report presents the design and implementation of an advanced electronic safe lock system utilizing a range of sensors and actuators for enhanced security. By integrating capacitive fingerprint sensors and numerical keypads, the system enhances authentication reliability and reduces false rejections and acceptances. Real-time monitoring with an ESP32 camera module and GPS tracking ensures continuous surveillance and immediate alerts in case of breaches. Visual and audible alerts through RGB LEDs and buzzers provide immediate feedback, while the incorporation of a WiFi module enables remote monitoring and control. These advanced techniques ensure consistent and accurate security measures, increasing efficiency and reducing the possibility of human error.